Environmental Impact of Irrigated Wheat Production System Using the life Cycle Assessment Technique (Case study: Ardabil province) - Jabraeil Taghinazhad (University of Tabriz, 2021)
AbstractBackground and Objective: Life Cycle Assessment (LCA) is an approach to study the environmental impacts of product production or activities that are calculated based on two indicators of resource consumption and emissions.One of the inputs using limitations in agriculture is environmental emissions of various pollutants that have negative effects on the environment. The purpose of this study is to investigate the environmental impacts for irrigated wheat production in Ardabil provience. Materials and Methods: This analysis considered the entire system which was required to produce one ton of wheat grain. For this purpose, a functional unit was assumed based on ISO14040 methods.The primary data were gathered using the questioners and face to face interview with 100 irrigated wheat producers in Ardabil Province in 2018. The environmental impacts were classified into seven impact categories including global warming, acidification, terrestrial eutrophication, depletion of fossil resources, depletion of phosphate, potassium resource depletion and water resource depletion by using LCA methodology. Results: The values for climate change (global warming), acidification and eutrophication, phosphate resource depletion, potassium resource depletion and water resource depletion were estimated at 0.075, 0.178, 0.401, 0.36, 0.628, 0.040, and 0.353, respectively. As a result, among environmental effect categories (EcoX) the highest environmental impacts were observed in the eutrophication categories; among the resource depletion categories (RDI), the depletion of phosphate resources had the greatest negative environmental impact for irrigated wheat production. Conclusion: It seems that the management of optimal use of chemical fertilizers, specially nitrogen fertilizer and replacing them with a variety of organic fertilizers and using the bio-fertilizers can reduce the negative environmental impacts of irrigated wheat producers in terms of terrestrial eutrophication and phosphorus fertilizers groups in Ardabil Province.